Applying Scanning And Skimming Techniques for Reading Comprehension Course of 6 Grade Students of Elementary School - Chindy Hanggara Rosa; Marsuki Marsuki (UIBU, 2023)
Reading is the activity or skill of understanding written words. According to Grabe and Stoller (2002:17), “Reading comprehension as the ability of understanding and interpreting information in a text correctly which makes the readers has understood what they will read in the text. The objectives of the study are 1) to know at the students’ interest and capability in reading comprehension before being taught by using skimming and scanning techniques. 2) to know the students’ interest and capability in reading comprehension after being taught by using scanning and skimming techniques.In analyzing of this research, the writer applied the theory of scanning and skimming. According to Arundel and Study Skill Lab (1999) skimming is a strategy of rapidly moving the eyes over the text with the purpose of getting only the main idea and general overview of the content. In addition, according to Maxwell (1970), scanning is to get specific information within a text such as dates, names, places, specific dates, and details quickly. They are regarded as desirable reading skill and is taught in developing reading. In conducting this research, the researcher used class action research that consists of Reconnaissance steps for observing the situation in order to identify the problem. Then the cycle was divided into four stages; planning to choose an action and prepare teaching materials and instruments of gathering data observing, acting by teaching reading comprehension using scanning and skimming techniques and asking students to compose, observing during the action, reflecting to sort and analyze data conclude and get an evaluation to ide the next planning.The result of the 1 cycles shows that the use of scanning and skimming techniques could improve students’ interest and capability in reading comprehension. The students got improvement in finding the main idea and specific information such as name, date, price, and number from the contents rapidly by moving their eyes. The students were motivated to be active in the classroom activities. They got a better score In conclusion, this class action research shows that using scanning and skimming techniques in teaching reading is a success. Therefore, it is important for teachers, university students, and further researchers to know and apply these techniques in teaching reading